Delivery routes in pregnancy with COVID-19 and the risk of intrapartum vertical transmission: a meta-analysis (Medical Journal of Indonesia, 2021)
BACKGROUND Mode of delivery has become an important highlight in managing pregnancy with coronavirus disease 2019 (COVID-19) due to the possible risk of viral transmission from mother to baby, especially during the peripartum period. This study aimed to review the mode of delivery and the possible risk of vertical transmission related to delivery routes in pregnant women with COVID-19. METHODS Literature research was conducted using PubMed, Scopus, Embase, and EBSCO database with the following keywords: SARS-CoV-2, COVID-19, pregnancy, vertical transmission, and delivery. The extracted data were as follows: author, country, study design number of cases, maternal age, mode of delivery, and the SARS-CoV-2 status in neonates. RESULTS Of 11 studies found, vaginal birth was reported in 218 cases (34.53%) and cesarean delivery was reported in 385 women (65.47%). The indication for cesarean delivery was majority due to COVID-19 related condition (53.61%). In total, 8 neonates who confirmed positive for COVID-19 by real-time polymerase chain reaction assay were reported. The pooled odds ratio (95% confidence interval) for SARS-CoV-2-positive neonates in cesarean delivery compared with vaginal birth was 0.622 (0.237–1.633) with p = 0.335. CONCLUSIONS Cesarean delivery is more common than vaginal delivery in patient with SARS-CoV-2 infection. Any delivery route is not related to possible risk of intrapartum vertical transmission, and cesarean delivery should be carried out based on the obstetric indication.